Method for the elaboration of the curriculum, based on competences in the teaching of general physics in the Faculty of Chemical and Textile Engineering of the National University of Engineering - Sánchez Dávalos, Juan (2018)
It is proposed a competence of educational methodology starting from the subject "Thermodynamic Laws" of the syllabus of the Physics II course which is taught to the students of the Faculty of Chemical and Textile Engineering of the Universidad Nacional de Ingeniería (UNI). This competence approaches the development of the training project "Implementation of culture in thermodynamics", which allows the students of the Faculty to interpret and search solutions to a current problem, such as the environmental pollution generated by the car park in Lima. The development of the proposed competence involves the: 1 / elaboration of a matrix of the project, 2 / constitution of a working group (4 students), 3 / planning of the collaborative works, 4 / follow-up of the group meeting work, 5 / reporting, and 6 / qualification of the collaborative work.